The development of the method of ratings formation of scientific and scientific-pedagogical staff publication activity - Kuzmin, Oleh; Zhuk, Liliya (Technology audit and production reserves, 2017)
The analysis of the publication activity of domestic universities according to SciVerse Scopus scientometric database is conducted and its dependence on the effectiveness of the motivation systems in these universities is established. The necessity of rating the publication activity of scientific and scientific-pedagogical workers of higher educational institutions as effective ways of ensuring the competitiveness of universities, providing and improving the presence in international and domestic universities rankings is substantiated. The positive experience of managing the publication activity on the example of the Taras Shevchenko National University of Kyiv and the "Lviv Polytechnic" National University is shown. The methodology for the formation of the rating of the SSPS publication activity by the indicator is developed, which is calculated as the average number of scientific publications (monographs, articles, conference proceedings) for a certain period. It is shown that the indicators of publication activity and citation indexes are not the only and final criteria for assessing scientific results, but only an instrument for supporting decision-making by experts. Measures are developed to strengthen the publication activity.